In-situ hydration studies of C4AF at early ages in the presence of other phases - Cuesta-García, Ana María; Santacruz-Cruz, María Isabel; Fauth, François; Gómez-de-la-Torre, María de los Ángeles; García-Aranda, Miguel Ángel (My University, 2015)
The ferrite phase, C4AF in cement nomenclature, also called brownmillerite, is the major iron-containing phase in Ordinary Portland Cement (OPC) and in iron rich belite calcium sulfoaluminate cements. The term “ferrite” usually refers to a solid solution with a wide range of composition with the general formula Ca2(AlyFe2−y)O5, where y can vary from 0 to about 1.33 [1]. In cement chemistry the ideal composition C4AF (4CaO•Al2O3•Fe2O3), is used to describe the ferrite phase in Portland cement. The hydration of pure brownmillerite with water initially forms metastable C-(A,F)-H hydrates which eventually convert to a hydrogarnet phase C3(A,F)H6 (katoite) over time. The addition of calcium sulfates to C4AF inhibits the direct hydration of C4AF to C3(A,F)H6. Ettringite (AFt) is the most commonly hydration product observed under these conditions. In addition, ettringite could decompose to an AFm monosulfoaluminate hydrate [2]. The aim of this work is to better understand the early age hydration of tetracalcium aluminoferrite phase in the presence of other phases at early ages in order to understand “eco-cement” performances. Chiefly, we want to determine the hydration kinetic and mechanisms of this phase using different reaction media. Firstly, C4AF in the presence of water hydrates to form mainly a hydrogarnet-type phase C3(A,F)H6. The hydration of ferrite with w/s ratio of 1.0 yielded C3A0.84F0.16H6 as single crystalline phase. Its crystal structure has been determined by the Rietveld method. Figure 1 shows the Rietveld synchrotron X-ray powder diffraction plot for this sample. Secondly, we have observed that the presence of sulfates strongly modifies ferrite hydration behavior. The hydration of C4AF in the presence of gypsum gives AFt and, once gypsum is completely dissolved, crystalline AFm starts to precipitate. Figure 2 shows a selected range of the SXRPD raw patterns for C4AF_st-C4A3S-g-1.0 (sample with C4AF, gypsum and ye’elimite) recorded at different time of hydration, with the main peaks due to a given phase labelled. Finally, the effect of w/s ratio has also been studied for this sample. Results indicate that higher amounts of water favour the formation of AFm. A summary of the results for the hydration of C4AF will be discussed. Figure 1. Rietveld Synchrotron X-Ray Powder Diffraction plot for C3A0.84F0.16H6. The tic marks are the Bragg reflections: C3A0.84F0.16H6 (lower row); Quartz, internal standard (upper row).
Cartel presentado en congreso
Keywords: Cemento; Rietveld method; Eco-cementos; Synchrotron